BENCHMARKING – THE INSTRUMENT OF COMPETITIVE ADVANTAGES DEVELOPMENT - Karas, Olena (Journal of European Economy, 2017)
The theoretical foundations of benchmarking and its application and vectors of development in the economy are substantiated. The concept and types of benchmarking, methods of research, analysis of environment, development and implementation of benchmarking in a company are studied. The author characterizes the circle of questions that can be settled by using benchmarking techniques. Benchmarking is just developing in Ukraine. It is an important factor of economic development. The usefulness of benchmarking consists in the fact that production processes, trading operations and marketing functions are best managed if the company analyses and implements best practices, methods and technologies of the leading enterprises or industries. The author offers to use benchmarking as an effective instrument of the world economy.